Philosophy of the Bhagavad Gita: A Contemporary Introduction, by Keye Maitra - Anandakichenin, Suganya (Religions of South Asia, 2021)
Philosophy of the Bhagavad Gita: A Contemporary Introduction, by Keye Maitra. London: Bloomsbury, 2018. 204 pp., £54 (hb), £17.09 (pb), £13.67 (eBook). ISBN: 978-1-35-004019-9 (hb), 978-1-35-004018-2 (pb), 978-1-35-004017-5 (eBook).